Method for constructing and forming particle reinforced aluminum-based composite material

By using an aluminum alloy intermediate layer in the particle-reinforced aluminum-based composite material and performing thermal isostatic pressure treatment, the problems of serious interface reactions and many defects during welding are solved, and high-strength large-size composite material connection and material utilization rate are achieved Improvement.

CN119464815APending Publication Date: 2025-02-18ZHONGKE COMPOSITE (BINZHOU) NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411604883.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing particle-reinforced aluminum-based composite materials are prone to defects such as severe interface reactions, holes and cracks during welding, resulting in low joint strength, limited base material specifications, and high loss rate of processing materials for special-shaped parts.

Method used

Aluminum alloy is used as the intermediate layer to connect multiple aluminum-based composite materials with different particle contents, and through thermal isostatic pressure treatment, the interfaces are closely connected under high temperature, high pressure and vacuum conditions to avoid the occurrence of holes and cracks.

Benefits of technology

The density and bonding strength of the interface bonding of composite materials are improved, the degree of interface reaction is reduced, the reliable connection of large-size composite materials is achieved, the material utilization rate is improved, and the loss of materials processed by special-shaped parts is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464815A_ABST
    Figure CN119464815A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of material preparation, and particularly relates to a method for constructing and forming a particle-reinforced aluminum-based composite material, which comprises the following steps: cutting a particle-reinforced aluminum-based composite material blank, and removing oxide skin; then selecting an aluminum alloy sheet with the same specification as the composite material bonding surface as a middle layer; and a plurality of composite materials containing the aluminum alloy middle layers are assembled according to large-size blanks or special-shaped part blanks and then packaged and sleeved for hot isostatic pressing, and the constructed and formed large-size or special-shaped aluminum-based composite material blanks can be obtained. The aluminum-based composite material is constructed and formed, and the problems that an existing aluminum-based composite material is difficult to prepare in a large size, and materials are wasted when large-size special-shaped parts are machined are solved. Compared with a traditional welding method which is difficult to perform high-strength connection on the particle reinforced aluminum-based composite material, the method has the advantages of no defect at the joint, high connection strength, improvement of the material utilization rate and easier realization of preparation of large-size part blank materials, and compared with a traditional welding method which is difficult to perform high-strength connection on the particle reinforced aluminum-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a method for constructing and molding a particle-reinforced aluminum-based composite material. Background Art

[0002] Particle-reinforced aluminum-based composites inherit the mechanical and physical properties of aluminum alloys and reinforced materials, showing high specific strength, high specific modulus, wear resistance, low expansion, high thermal conductivity and special functional characteristics, and under the composite effect, they produce good advantages such as fatigue resistance, creep resistance, heat resistance, and vibration reduction. They have broad application prospects in high-precision electromechanical products, space optical instruments, inertial navigation instruments, rail transit and ground transportation equipment, electronic devices, communication facilities, new light sources, microwave devices and other fields.

[0003] Existing particle-reinforced aluminum-based composite materials are limited by the preparation process and production equipment, making it difficult to achieve large-scale composite materials, and are usually connected by welding. The welding methods of particle-reinforced aluminum-based composite materials mainly include fusion welding, brazing, stir friction welding and diffusion welding. For fusion welding, during the crystallization process of the molten pool, the melting point of the ceramic reinforcement phase of SiCp / Al is much higher than that of the matrix. When the heating temperature exceeds 640°C, the Al in the matrix will react with SiC to form Al4C3 brittle compounds, which seriously affect the joint performance. In addition, with the increase of the content of reinforcing particles, the viscosity of the molten pool is aggravated, resulting in an increase in defects such as pores and cracks. For brazing, the mechanical properties of the joint after welding are generally lower than those of the composite parent material. Limited by the performance of the brazing filler metal, it is often difficult to apply to structures with high strength requirements; and with the increase of ceramic particles, the wettability between the parent material and the brazing filler metal is poor.

[0004] CN117245201A uses aluminum powder and reinforcing particles as a mixed intermediate layer, and then stirs and welds them. With this method, the weight fraction of the reinforcing phase is no more than 30%, and it is only suitable for thin plate welding. CN110293304B uses inert reinforcing phases such as Al2O3 and TiB2 as an intermediate layer, and welds them through an electron beam. With this method, the volume fraction of the reinforcing phase is no more than 40%. In addition, the weldable composite material is small in size, making it difficult to achieve large-size, high-volume aluminum-based composite material welding.

[0005] In summary, a new connection process is urgently needed to improve the problems of aluminum-based composite materials with different volume fractions in the traditional welding process, such as easy appearance of holes, harmful interface reactions, low bonding strength and limited welding specifications, so as to achieve effective connection of multiple composite materials, improve the density and bonding strength of the joints, reduce the degree of interface reaction of composite materials, achieve the reliability of large-size composite material connections, improve material utilization, and reduce the material loss rate in the processing of large-size special-shaped components. Summary of the invention

[0006] The embodiment of the present invention provides a method for constructing and forming a particle-reinforced aluminum-based composite material, which aims to solve the problems of severe interface reaction, many defects such as holes, low joint bonding strength, limited parent material specifications and high material loss rate in the processing of composite material special-shaped parts in the current composite material welding process.

[0007] The embodiment of the present invention is implemented as follows:

[0008] A method for constructing a particle-reinforced aluminum-based composite material, comprising:

[0009] Step 1: obtaining a pure composite material surface with a reinforcing particle volume fraction of 0 to 75% and half-exposed reinforcing particles;

[0010] Step 2: Select a pure surface of an aluminum alloy intermediate layer with a thickness of 0.1 mm to 0.5 mm according to the maximum particle size of the composite material reinforcement particles;

[0011] Step 3: Arrange multiple composite materials in order, place an aluminum alloy middle layer between adjacent composite materials, fix the composite materials and the aluminum alloy middle layer, and perform a hot isostatic pressing treatment with a package sleeve;

[0012] Step 4: Remove the surface aluminum alloy sheath by physical means to obtain the constructed particle-reinforced aluminum-based composite material.

[0013] Furthermore, the pure metal surface of the composite material is subjected to alkaline etching treatment, specifically:

[0014] Step 1: Use the base element to alkaline wash with a sodium hydroxide solution with a concentration of 100-300g / L for 10-40min;

[0015] Step 2: Place the composite material in a nitric acid solution with a concentration of 150-450 g / L and wash for 5-20 minutes.

[0016] Step 3: Obtain a composite material with a surface roughness Ra satisfying 2 μm-10 μm.

[0017] Furthermore, the composite material and the aluminum alloy intermediate layer are fixed by welding.

[0018] Furthermore, the reinforcing particles are one or more of SiC, B4C and Si.

[0019] Furthermore, the pure surface of the aluminum alloy intermediate layer is subjected to a degreasing treatment, specifically:

[0020] Step 1: Soak the aluminum alloy middle layer in a sodium hydroxide solution with a concentration of 50-200g / L for degreasing for 0.5-3min;

[0021] Step 2: Wash the surface of the aluminum alloy middle layer with clean water, and then neutralize it with 100-500g / L nitric acid solution to obtain a smooth and shiny aluminum alloy middle layer.

[0022] Furthermore, the aluminum alloy sheath has a thickness of 3-10 mm, and the aluminum alloy sheath is subjected to vacuum degassing treatment at 400-500° C. until the vacuum degree in the aluminum alloy sheath reaches 10 -2 After reaching Pa, continue to keep warm for 3-20h and then seal the package and take it out of the oven.

[0023] Furthermore, the hot isostatic pressing is specifically:

[0024] Step 1: The temperature is raised from 10-40°C to 450-520°C, and then kept warm for 1-4 hours, wherein the heating rate is 1-5°C / min;

[0025] Step 2: The temperature is raised from 450-520°C to 580-640°C and kept for 3-10 hours, wherein the heating rate is 0.5-2.0°C / min and the pressure is 100-200MPa.

[0026] Furthermore, the physical method of removing the surface aluminum alloy sheath is specifically to remove the surface aluminum alloy sheath by turning or milling.

[0027] The present invention uses aluminum alloy as an intermediate layer to connect multiple aluminum-based composite materials with different particle contents, and performs hot isostatic pressing to achieve close connection of the interface of the composite materials under high temperature, high pressure and vacuum conditions, thereby avoiding the generation of holes and cracks.

[0028] By using hot isostatic pressing treatment, the furnace temperature and pressure can be precisely controlled to improve product quality. In addition, the aluminum alloy intermediate layer can produce a liquid phase at high temperature, which increases the wettability of the reinforcing particles in the semi-exposed state of the bonding surface and improves the strength of the bonding point.

[0029] Compared with the limitations of traditional welding methods, the use of hot isostatic pressing furnaces can achieve high-strength connections of large-sized composite materials and special-shaped parts. The diameter of the connected composite materials can be adjusted according to the size of the hot isostatic pressing furnace, and the composite special-shaped parts can be flexibly handled to reduce material losses during mechanical processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a flow chart of the method for constructing and forming the particle reinforced aluminum-based composite material provided by the present invention;

[0031] Figure 2 It is the metallographic structure diagram of the first embodiment of the present invention;

[0032] Figure 3 is the XRD pattern of the first embodiment of the present invention;

[0033] Figure 4 is a physical diagram of a second embodiment of the present invention;

[0034] Figure 5 is a metallographic structure diagram of a second embodiment of the present invention;

[0035] Figure 6 It is a physical diagram of the third embodiment of the present invention.

[0036] Figure 7 is an X-ray diagram of a third embodiment of the present invention;

[0037] Figure 8 This is a physical diagram of the fourth embodiment of the present invention

[0038] Fig. 9 FIG. 1 is a processing sample diagram of the fourth embodiment of the present invention DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0040] By using aluminum alloy as an intermediate layer to connect aluminum-based composite materials with different particle contents and undergoing hot isostatic pressing, it is possible to achieve a tight connection of the interface of the composite material under high temperature, high pressure and vacuum conditions, thereby avoiding the generation of holes and cracks.

[0041] The temperature and pressure of the hot isostatic pressing furnace are precisely controllable, which improves product quality. In addition, a liquid phase can be generated in the middle of the aluminum alloy at a high temperature, which increases the wettability of the reinforcing particles in the semi-exposed state of the bonding surface and improves the strength of the bonding point.

[0042] Embodiment 1

[0043] Reference Figure 1 In an embodiment of the present invention, a method for constructing a particle-reinforced aluminum-based composite material is provided, comprising:

[0044] S101: obtaining a pure composite material surface with a reinforcing particle volume fraction of 0 to 75% and half-exposed reinforcing particles;

[0045] S102: Selecting a pure surface of an aluminum alloy intermediate layer with a thickness of 0.1-0.5 mm according to the maximum particle size of the composite material reinforcement particles;

[0046] S103: placing multiple composite materials in order, placing an aluminum alloy middle layer between adjacent composite materials, fixing the composite materials and the aluminum alloy middle layer, and performing a package hot isostatic pressing process;

[0047] S104: The surface aluminum alloy sheath is removed by physical means to obtain a constructed particle-reinforced aluminum matrix composite material.

[0048] In S101, the volume fraction of the reinforcing particles can be 0, 60%, or 75%, and the specific content can be selected according to actual needs; in step S102, aluminum alloy intermediate layers of different thicknesses are selected according to the maximum particle size of the composite material reinforcing particles. It should be explained that the composite material reinforcing particles can be one or more of SiC, B4C, and Si, and the maximum particle size refers to the maximum particle size within one or more of SiC, B4C and Si. For example, when the maximum particle size of one or more of SiC, B4C and Si is not greater than 20μm, the thickness of the aluminum alloy intermediate layer is selected to be 0.1mm, and when the maximum particle size of the reinforcing particles is not greater than 50μm or is 100μm, the thickness of the aluminum alloy intermediate layer is 0.5mm. The above are specific examples of the thickness of the aluminum alloy intermediate layer, and the specific thickness of the aluminum alloy intermediate layer can be selected according to actual needs.

[0049] Specifically, in the first embodiment, two pieces of 60 vol.% SiC / Al composite materials with a size of φ160 mm×40 mm were selected for alkaline etching, wherein the concentration of sodium hydroxide was 100 g / L, the etching time was 40 min, and then after being rinsed with clean water, they were cleaned with 150 g / L nitric acid solution for 20 min, and the dust on the surface of the composite material was cleaned with a high-pressure water gun to obtain a pure surface of the composite material with a roughness Ra of 8.7 μm.

[0050] Since the SiC particle size used in the 60 vol.% SiC / Al composite material can reach 100 μm, 1060Al with a size of φ160 mm × 0.5 mm is selected as the middle layer. It is first degreased in a 50 g / L sodium hydroxide solution for 3 minutes, and then neutralized in a 100 g / L nitric acid solution to obtain a smooth, glossy 1060Al middle layer without oxide film.

[0051] The degreased 1060Al middle layer is placed in the middle of the composite material after alkali etching and fixed by spot welding. Then the composite material to be constructed is covered with 3mm 1060Al, and then a stainless steel exhaust pipe with an inner diameter of 10mm is welded.

[0052] The package was placed in a tabletop resistance furnace for heating. Before heating, the stainless steel vacuum pipe was connected to a Roots pump for vacuuming. The package was then heated from 22°C to 450°C in 2h and then kept warm. When the vacuum degree was 3.2×10 -2 Pa, start timing, and after 3h of heat preservation, the vacuum degree is 2.8×10 -2Pa, then seal the package and cool to room temperature.

[0053] The constructed composite material cooled to room temperature is loaded into a hot isostatic pressing furnace. The hot isostatic pressing gas is argon with a purity of more than 99.99%. The temperature is raised from 27°C at a rate of 5°C / min. The temperature is raised to 480°C and then kept warm, and the pressure is maintained at 80MPa. After keeping warm for 3 hours, the temperature is raised at 2°C / min. After the temperature is raised to 620°C, it is kept warm for 3 hours and the pressure is maintained at 100MPa. After the insulation and pressure holding are completed, the temperature and pressure programs are turned off. The constructed blank is taken out of the furnace when it is cooled to 185°C. After being taken out of the furnace, the constructed composite material continues to cool to room temperature. The 1060Al sheath is milled off with a milling machine to obtain a constructed 60vol.% SiC / Al composite material.

[0054] The 60 vol. % SiC / Al composite material prepared in this embodiment is Figure 2 There are no defects such as holes and cracks under the metallographic structure shown. Figure 3 The XRD analysis shown in the figure shows that no harmful phase of Al4C3 is found, and the flexural strength is 404MPa, which is higher than the flexural strength requirement of 360MPa for high volume fraction aluminum-based composite materials in GB / T41736-2022.

[0055] In the second embodiment, two pieces of 27wt.% Si / Al composite materials of 190mm×120mm×35mm and 50wt.% Si / Al of 190mm×120mm×35mm were selected for alkaline etching, wherein the concentration of sodium hydroxide was 200g / L, and the etching time was 20min. Then, after being rinsed with clean water, they were cleaned with 300g / L nitric acid solution for 10min. The surface of the composite material was cleaned with a high-pressure water gun to obtain a pure surface of the composite material with a roughness Ra of 3.1μm.

[0056] Since the maximum Si particles of 27% Si / Al and 50% Si / Al are no larger than 20μm, two pieces of 4047Al with specifications of 190mm×120mm×0.1mm are taken as the middle layer. The aluminum alloy middle layer is first degreased in 150g / L sodium hydroxide solution for 2.5min, and then neutralized in 300g / L nitric acid solution to obtain a smooth, glossy 4047Al middle layer without oxide film.

[0057] The two degreased 4047Al intermediate layers were placed between the 27wt.%Si / Al and 50wt.%Si / Al after alkaline etching, and the composite material and the intermediate layer were fixed by spot welding. Then, a 5mm 1060Al was used to encapsulate the composite material to be constructed, and a stainless steel exhaust pipe with an inner diameter of 10mm was welded after the encapsulation. Then, the encapsulation was placed in a desktop resistance furnace for heating. Before heating, the stainless steel exhaust pipe was connected to a Roots pump for vacuuming, and then the encapsulation was heated. The encapsulation was heated from 21℃ to 520℃ in 2.5h and then kept warm. When the vacuum degree was 4.3×10 -2 Pa, start timing, and after 6 hours of heat preservation, the vacuum degree is 1.6×10 -2 Pa, seal the package, take it out of the oven, and cool it to room temperature.

[0058] The molding composite material cooled to room temperature is loaded into a hot isostatic pressing furnace. The hot isostatic pressing gas is argon with a purity of more than 99.99%. The temperature is raised from 34°C at a rate of 1°C / min. When the temperature reaches 450°C, insulation is started and the pressure is maintained at 80MPa. After insulation for 1 hour, the temperature is raised at a rate of 0.5°C / min. After the temperature reaches 575°C, insulation is carried out for 6 hours and the pressure is maintained at 200MPa. After the insulation and pressure are completed, the temperature and pressure programs are closed and the molding batch is taken out of the furnace when it cools to 163°C.

[0059] The molded composite material was further cooled to room temperature after being taken out of the furnace, and the 1060Al sheath was removed by a milling machine to obtain a molded (27-50) wt.% Si / Al gradient composite material.

[0060] The (27-50) wt.% Si / Al gradient composite material prepared by this embodiment is as follows Figure 4 As shown. Figure 5 Metallographic structure observation revealed that the interface was well bonded, with no defects such as holes or cracks at the joint, and the bending strength of the joint could reach 364MPa.

[0061] In the third embodiment, two pieces of 50wt.% B4C / Al composite materials with a size of 80mm×70mm×35mm were selected for alkaline etching, wherein the concentration of sodium hydroxide was 300g / L, the etching time was 10min, and then after being rinsed with clean water, they were cleaned with a 450g / L nitric acid solution for 5min, and the surface of the composite material was cleaned with a high-pressure water gun to obtain a composite material surface with a roughness Ra of 5.5.

[0062] Since the largest B4C particle of 50wt.% B4C / Al is no larger than 50μm, two pieces of 6061Al with specifications of 70mm×35mm×0.25mm are used as the middle layer. They are first degreased in a 200g / L sodium hydroxide solution for 0.5min, and then neutralized in a 500g / L nitric acid solution to obtain a smooth, glossy 6061Al middle layer without oxide film.

[0063] The degreased 6061Al intermediate layer is placed between the 50wt.% B4C / Al after alkaline etching, and the composite material and the intermediate layer are fixed by spot welding. Then a 10mm 1060Al is used to encapsulate the composite material to be constructed, and a stainless steel exhaust pipe with an inner diameter of 10mm is welded after the encapsulation. Then the encapsulation is placed in a desktop resistance furnace for heating. Before heating, the stainless steel exhaust pipe is connected to a Roots pump for vacuuming, and then the encapsulation is heated. The encapsulation is heated from 33°C to 480°C in 2.5h and then kept warm. When the vacuum degree is 3.1×10 -2 Pa, start timing, and after 10h of heat preservation, the vacuum degree is 2.2×10 -2 Pa, seal the package, take it out of the oven, and cool it to room temperature.

[0064] The composite material to be molded is cooled to room temperature and is loaded into a hot isostatic pressing furnace. The hot isostatic pressing gas is argon with a purity of more than 99.99%. The temperature is raised from 27°C at a rate of 3°C / min. When the temperature reaches 520°C, insulation is started and the pressure is maintained at 80MPa. After insulation for 4 hours, the temperature is raised at a rate of 1°C / min. When the temperature reaches 640°C, insulation is performed for 10 hours and the pressure is maintained at 150MPa. After the insulation and pressure are completed, the temperature and pressure programs are closed and the molded blank is taken out of the furnace when it cools to 193°C.

[0065] The molded composite material after being taken out of the furnace was further cooled to room temperature, and the 1060Al sheath was removed by a milling machine to obtain a molded 50wt.% B4C / Al composite material.

[0066] The 50wt.% B4C / Al composite material prepared by this embodiment is as follows Figure 6 As shown, the internal metallurgical quality meets the aviation Class I casting standards specified in HB 963. The radiographic flaw detection negative is shown in Figure 7 As shown, the interface is well bonded and there are no defects such as holes or cracks at the joint.

[0067] In the fourth embodiment, a 65 vol.% SiC / Al composite material of 75 mm×50 mm×50 mm was selected, of which 10 mm×10 mm×50 mm strips were cut off at four corners, and filled with 4 pieces of 20 vol.% SiC / Al of 10 mm×10 mm×50 mm. The composite material of the above two components was alkaline etched, with a sodium hydroxide concentration of 150 g / L and an etching time of 30 min. After being rinsed with clean water, it was cleaned with a 250 g / L nitric acid solution for 15 min, and then the surface of the composite material was cleaned with a high-pressure water gun to remove dust. The surface roughness Ra of the obtained 65 vol.% SiC / Al and 20 vol.% SiC / Al was 9.3 and 2.7 respectively.

[0068] The maximum SiC particles of 65vol.%SiC / Al and 20vol.%SiC / Al can reach 150μm, so 1060Al with a specification of 50mm×10mm×0.5mm and 8 pieces are selected as the middle layer. They are first degreased in a 100g / L sodium hydroxide solution for 2min, and then neutralized in a 200g / L nitric acid solution to obtain a smooth, glossy 1060Al middle layer without oxide film.

[0069] The degreased 1060Al intermediate layer is placed between the 65vol.%SiC / Al and 20vol.%SiC / Al after alkaline etching, and the composite material and the intermediate layer are fixed by spot welding. Then, a 5mm 1060Al is used to encapsulate the composite material to be constructed, and a stainless steel exhaust pipe with an inner diameter of 10mm is welded after the encapsulation. Then, the encapsulation is placed in a desktop resistance furnace for heating. Before heating, the stainless steel exhaust pipe is connected to a Roots pump for vacuuming, and then the encapsulation is heated. The encapsulation is heated from 29℃ to 500℃ in 2.5h and then kept warm. When the vacuum degree is 4.4×10 -2 Pa, start timing, and after 8 hours of heat preservation, the vacuum degree is 3.7×10 -2 Pa, seal the package, take it out of the oven, and cool it to room temperature.

[0070] The composite material to be molded and cooled to room temperature is loaded into a hot isostatic pressing furnace. The hot isostatic pressing gas is argon with a purity of more than 99.99%. The temperature is raised from 31°C at a rate of 2°C / min. When the temperature reaches 500°C, insulation is started and the pressure is maintained at 80MPa. After insulation for 2h, the temperature is raised at a rate of 2°C / min. After the temperature reaches 600°C, insulation is carried out for 8h and the pressure is maintained at 180MPa. After the insulation and pressure are completed, the temperature and pressure programs are closed and the molded blank is taken out of the furnace when it cools to 177°C.

[0071] The composite material is further cooled to room temperature after being taken out of the furnace, and the 1060Al jacket is removed by a milling machine to obtain a composite material such as Figure 8 As shown, wire cutting and CNC milling are performed to obtain the processed samples, and the molding materials and samples are constructed as shown Fig. 9 shown.

[0072] In the description of this specification, the description with reference to the terms "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0073] In addition, the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for constructing a particle-reinforced aluminum-based composite material, characterized in that: Construction methods include: Obtaining a composite material surface that is pure and semi-exposed with reinforcement particles and has a reinforcement particle volume fraction of 0 to 75%; Select a 0.1mm-0.5mm aluminum alloy intermediate layer pure surface according to the maximum particle size of the composite material reinforcement particles; Placing multiple composite materials in order, placing an aluminum alloy middle layer between adjacent composite materials, fixing the composite materials and the aluminum alloy middle layer and performing a hot isostatic pressing treatment with a package sleeve; The aluminum alloy sheath on the surface is removed by physical methods to obtain a constructed particle-reinforced aluminum-based composite material.

2. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The pure metal surface of the composite material is subjected to alkaline etching treatment, specifically: The base element is alkaline-etched and washed with a sodium hydroxide solution having a concentration of 100-300 g / L for 10-40 minutes; The composite material is then placed in a nitric acid solution with a concentration of 150-450 g / L for cleaning for 5-20 minutes. A composite material with a surface roughness Ra satisfying 2μm-10μm is obtained.

3. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The composite material and the aluminum alloy intermediate layer are fixed by welding.

4. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The reinforcing particles are one or more of SiC, B4C and Si.

5. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The pure surface of the aluminum alloy intermediate layer is subjected to a degreasing treatment, specifically: The aluminum alloy middle layer is immersed in a sodium hydroxide solution with a concentration of 50-200 g / L for degreasing for 0.5-3 min; The surface of the aluminum alloy intermediate layer is washed with clean water and then neutralized with 100-500g / L nitric acid solution to obtain a smooth and glossy aluminum alloy intermediate layer.

6. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The aluminum alloy sheath has a thickness of 3-10 mm. The aluminum alloy sheath is subjected to vacuum degassing treatment at 400-500°C. When the vacuum degree in the aluminum alloy sheath reaches 10 -2 After reaching Pa, continue to keep warm for 3-20h and then seal the package and take it out of the oven.

7. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The hot isostatic pressing is specifically: Step 1: The temperature is raised from 10-40°C to 450-520°C, and then kept warm for 1-4 hours, wherein the heating rate is 1-5°C / min; Step 2: The temperature is raised from 450-520°C to 580-640°C and kept for 3-10 hours, wherein the heating rate is 0.5-2.0°C / min and the pressure is 100-200MPa.

8. The method for constructing a particle-reinforced aluminum-based composite material according to claim 1, characterized in that: The physical method of removing the surface aluminum alloy sheath is specifically to remove the surface aluminum alloy sheath by turning or milling.

Citation Information

Patent Citations

  • A SiC p Electron beam welding method for particle-reinforced aluminum matrix composites

    CN110293304B

  • Interlayer for welding aluminum-based composite material and manufacturing method and welding method thereof

    CN117245201A